2017
DOI: 10.1016/j.ceb.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of retromer in neuroprotection

Abstract: HighlightsIn the endosomal network retromer retrieves cargo away from the degradative pathway.Retromer dysfunction has been implicated in Parkinson’s disease through different mechanisms.These include changes in protein association, protein degradation and mitochondria quality control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 87 publications
0
63
0
Order By: Relevance
“…Remarkably, SNX-BARs could cooperate with both SNX27 and retromer in the recycling of ligands encompassing the SBM, PDZ-binding motif, or both motifs. Overall, our studies establish that SNX-BARs function as a direct cargo-selecting module for a large set of transmembrane proteins transiting the endosome, in addition to their roles in phospholipid recognition and biogenesis of tubular structures.have been linked with a variety of human diseases including Alzheimer's disease, Parkinson's disease, cancer, and diabetes [4,5].Key protein machineries important for the sequence-dependent recycling include the evolutionarily conserved retromer complex (vacuolar protein sorting 35 [VPS35]/VPS26/VPS29 in higher eukaryotes) [6][7][8], the recently discovered retriever [9], the WASH complex [10][11][12], and members of the Sorting Nexin family (SNX) [13][14][15]. A subset of SNX proteins possessing a Bin/Amphiphysin/Rvs (BAR) domain, in addition to the phox-homology (PX) domain, have been linked with the retromer complex.…”
mentioning
confidence: 58%
“…Remarkably, SNX-BARs could cooperate with both SNX27 and retromer in the recycling of ligands encompassing the SBM, PDZ-binding motif, or both motifs. Overall, our studies establish that SNX-BARs function as a direct cargo-selecting module for a large set of transmembrane proteins transiting the endosome, in addition to their roles in phospholipid recognition and biogenesis of tubular structures.have been linked with a variety of human diseases including Alzheimer's disease, Parkinson's disease, cancer, and diabetes [4,5].Key protein machineries important for the sequence-dependent recycling include the evolutionarily conserved retromer complex (vacuolar protein sorting 35 [VPS35]/VPS26/VPS29 in higher eukaryotes) [6][7][8], the recently discovered retriever [9], the WASH complex [10][11][12], and members of the Sorting Nexin family (SNX) [13][14][15]. A subset of SNX proteins possessing a Bin/Amphiphysin/Rvs (BAR) domain, in addition to the phox-homology (PX) domain, have been linked with the retromer complex.…”
mentioning
confidence: 58%
“… since endosomal proteins can be targeted to both the plasma membrane and the TGN, how are specific trafficking routes selected? why do viral and bacterial pathogens target endosomal trafficking pathways? Undoubtedly, answers to these questions will lead us to a better understanding of endosomal receptor trafficking and their functions in organismal development and human disease.…”
Section: Discussionmentioning
confidence: 99%
“…With TFEB playing a central role in adaptive responses to a variety of other cellular stresses (Napolitano and Ballabio, 2016), the synchronized transcriptional control of retromer expression, and hence cargo retrieval and recycling through the endosomal network, is likely to be an important process in the long-term adaptation of cells to these stresses. Finally, with clinical studies having revealed perturbed retromer function in age-related Alzheimer's and Parkinson's diseases (Small and Petsko, 2015;McMillan et al, 2017), the identification of a TFEB-retromer pathway may offer an unexplored strategy through which to enhance retromer expression and thereby increase its neuroprotective role in these and other neurological diseases.…”
Section: Tfeb and Tfe3 Regulate Retromer Expression Upon Nutrient Depmentioning
confidence: 99%
“…While it is clear that hundreds of diverse cargo proteins transit through these dynamic retrieval subdomains en route to the cell surface and the TGN (Burd and Cullen, 2014), how retromer function is regulated and how this impacts the function of the retrieval subdomain remains unclear. What is evident is that disruption of retrieval subdomain function, either through mutations and/or reduced expression of retromer and retromer accessory proteins, is associated with the pathoetiology of a number of neurological disorders that include Alzheimer's and Parkinson's diseases (Small and Petsko, 2015;McMillan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%